A Marble Head of Ares in the Old Archaeological Museum of Chalkis in Euboea, Greece - Ovadiah, Ruth; Ovadiah, Asher (Gerión. Revista de Historia Antigua, 2021)
This study engages with a marble head of Ares, currently on exhibition at the Old Archaeological Museum of Chalkis in Euboea, Greece. The head has been executed according to the finest tradition of Classical-Hellenistic Greek sculpture, creating a figure with theatrical and pathetic expressions, recalling the Skopadic trend. The lack of pupils may indicate that the head of the god is a pre-Hadrianic Roman copy of a Greek original from the 4th-2nd centuries BCE.
Keywords: Attica; Pre-Hadrianic; Pupils; Sfumato; Skopas; Skopadic